Telomere shortening impairs regeneration of the olfactory epithelium in response to injury but not under homeostatic conditions. - Masami Watabe-Rudolph (Public Library of Science (PLoS), 2011)
Atrophy of the olfactory epithelium (OE) associated with impaired olfaction and dry nose represents one of the most common phenotypes of human aging. Impairment in regeneration of a functional olfactory epithelium can also occur in response to injury due to infection or nasal surgery. These complications occur more frequently in aged patients. Although age is the most unifying risk factor for atrophic changes and functional decline of the olfactory epithelium, little is known about molecular mechanisms that could influence maintenance and repair of the olfactory epithelium. Here, we analyzed the influence of telomere shortening (a basic mechanism of cellular aging) on homeostasis and regenerative reserve in response to chemical induced injury of the OE in late generation telomere knockout mice (G3 mTerc(-/-)) with short telomeres compared to wild type mice (mTerc(+/+)) with long telomeres. The study revealed no significant influence of telomere shortening on homeostatic maintenance of the OE during mouse aging. In contrast, the regenerative response to chemical induced injury of the OE was significantly impaired in G3 mTerc(-/-) mice compared to mTerc(+/+) mice. Seven days after chemical induced damage, G3 mTerc(-/-) mice exhibited significantly enlarged areas of persisting atrophy compared to mTerc(+/+) mice (p = 0.031). Telomere dysfunction was associated with impairments in cell proliferation in the regenerating epithelium. Deletion of the cell cycle inhibitor, Cdkn1a (p21) rescued defects in OE regeneration in telomere dysfunctional mice. Together, these data indicate that telomere shortening impairs the regenerative capacity of the OE by impairing cell cycle progression in a p21-dependent manner. These findings could be relevant for the impairment in OE function in elderly people.